2014
DOI: 10.1542/peds.2014-0381
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a Pediatric Hospice Palliative Care Program Over 15 Years

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Palliative care is an increasingly important element of pediatric care for children with noncurable, terminal conditions. Freestanding hospices represent one model of care provision; however, little research on this approach has been conducted. WHAT THIS STUDY ADDS:This report documents the experience of North America' s first freestanding hospice over 15 years to better understand the characteristics of children and families enrolled and to establish baseline information for futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 25 publications
1
15
1
Order By: Relevance
“…To expand our understanding of PPC outcomes, we undertook a retrospective study of the Canuck Place Children's Hospice (CPCH) program over a 15-year period, reviewing the medical charts of the 672 children on the CPCH program from 1995 to 2010. 5 As a secondary analysis, we examined the role played by ongoing, routine ACP discussions in family decisions to forgo resuscitation attempts at the end of life in terminally ill children regardless of the presence of AD/DNAR orders. We found that many families requested Full Code intervention, but there were few actual resuscitation attempts.…”
Section: Methodsmentioning
confidence: 99%
“…To expand our understanding of PPC outcomes, we undertook a retrospective study of the Canuck Place Children's Hospice (CPCH) program over a 15-year period, reviewing the medical charts of the 672 children on the CPCH program from 1995 to 2010. 5 As a secondary analysis, we examined the role played by ongoing, routine ACP discussions in family decisions to forgo resuscitation attempts at the end of life in terminally ill children regardless of the presence of AD/DNAR orders. We found that many families requested Full Code intervention, but there were few actual resuscitation attempts.…”
Section: Methodsmentioning
confidence: 99%
“…13 A high frequency of non-oncological and neurological conditions has also been demonstrated by other groups. 10,13,15,18,19 Still, this group of patients is largely underrepresented in the literature on pediatric palliative care. 20 Families with children having diagnoses other than cancer report a lack of support in the medical system and benefit particularly from pediatric palliative care services.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…This is in contrast to other populations described, although these publications cover a longer time range. 11,15,24 One reason for this disproportion may also be that, in recent years, robust structures of specialized outpatient centers and networks for patients with, for example, cystic fibrosis or Duchenne muscular dystrophy have evolved. 25,26 These centers provide outpatient care from childhood to often adulthood and have been instrumental, for example, for the routine implementation of noninvasive positive pressure ventilation in these patients.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The range of symptoms experienced in paediatric palliative care differ however in cancer and non-cancer patients [ 22 ]. Taken into account that the majority of children in palliative care in North America have non-cancer diagnoses [ 23 , 24 ] it should be stated that this study does not cover the full range of symptoms that may be encountered in paediatric palliative care.…”
Section: Discussionmentioning
confidence: 99%